The Vacuolating Autotransporter Toxin (Vat) of Escherichia coli Causes Cell Cytoskeleton Changes and Produces Non-lysosomal Vacuole Formation in Bladder Epithelial Cells - Díaz, Juan Manuel; Dozois, Charles M.; Avelar-González, Francisco Javier; Hernández-Cuellar, Eduardo; Pokharel, Pravil; de Santiago, Alfredo Salazar; Guerrero-Barrera, Alma Lilian (Frontiers in Cellular and Infection Microbiology, 2020)
Urinary tract infections (UTIs) affect more than 150 million people, with a cost of over 3.5 billion dollars, each year. Escherichia coli is associated with 70%-80% of UTIs. Uropathogenic E. coli (UPEC) has virulence factors including adhesins, siderophores, and toxins that damage host cells. Vacuolating autotransporter toxin (Vat) is a member of serine protease autotransporter proteins of Enterobacteriaceae (SPATEs) present in some uropathogenic E. coli (UPEC) strains. Vat has been identified in 20%-36% of UPEC and is present in almost 68% of urosepsis isolates. However, the mechanism of action of Vat on host cells is not well known. Thus, in this study the effect of Vat in a urothelium model of bladder cells was investigated. Vat was found to induce vacuole formation on the urothelium model, as well as cell rounding and loss of normal cell distribution. Different toxin concentrations were tested for different time periods, resulting in 15%-47% cytotoxicity as measured by the LDH assay. The damage observed was time and concentration-dependent. Cellular damage was also evaluated by the identification of cytoskeleton changes produced by Vat. Changes in the cytoskeleton of cells were observed with a different distribution of actin and loss of their stress fibers. Vat also modified the distribution of tubulin and Arp3. To evaluate the nature of the vacuoles generated by Vat, the Lamp-1 marker for the detection of lysosomes was used. Cells treated with Vat showed a decrease in lysosomes after toxin exposition, suggesting that vacuoles formed were not lysosomes. An ex vivo experiment with mouse bladder exposed to Vat resulted in the loss of integrity of the urothelial cells compared with the control bladder, suggesting alterations in the intercellular junctions. In conclusion, Vat demonstrates cytotoxic activity on bladder cells, in a time and concentration-dependent fashion. Also, Vat induces cell rounding associated with changes in the cytoskeleton distribution. Finally, vacuoles formed by Vat seem to be non-lysosomal vacuoles.